Diels–Alder reactions of an elusive 1, 3-butadiene bearing 2-carboxy and 4-alkoxy substituents. Issue 38 (21st September 2016) - Chen, Szu-Han; Chang, Che-Hsuan; Fang, Jim-Min
Graphical abstract: Highlights: An elusive 1, 3-butadiene having 2-carboxy and 4-alkoxy substituents is prepared. This reactive diene is trapped with dienophiles to give cycloaddition products. The cycloadduct from fumarate ester can be elaborated to oseltamivir (Tamiflu). Abstract: A reactive diene, ethyl 2-methylene-4-(pent-3-oxy)but-2-enoate, bearing electron-withdrawing carboxy and electron-donating pentoxy substituents is prepared and trapped in situ by a variety of dienophiles to form [4+2] cycloaddition products. Diels–Alder reaction of this diene with fumarate esters gives multiply substituted cyclohexenes that are useful for building the scaffold of oseltamivir.